Pengaruh Penggunaan Informasi Akuntansi Terhadap Keberhasilan Usaha Kecil Menengah (Studi Pada Sentra Konveksi di Kecamatan Tingkir Kota Salatiga) - Alex Wibowo; Elisabeth Penti Kurniawati (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
Accounting information can be used as a basis for business decisions making. Making the right decision can determine the success of a business. Therefore, accounting information has an important role toward the business success. Based on previous studies, SMEs often face difficulties to apply accounting in their business. However, the SMEs can still run their business. The aim of this study is to prove the effect of accounting information utilization toward the business success of SMEs. The research objects are SMEs on convection center in Tingkir Salatiga, which is one of SMEs center that still exist in Salatiga until now. The sampling method used in this research is purposive sampling, with SMEs that already have accounting information as the criteria, so it can be further investigated regarding the use of the accounting information in the business. The results showed that the accounting information utilization affect the business success in the convection center. Therefore, SMEsshould use accounting information as a basis for business decisions making in order to obtain appropriate decision so that support its business success.